Pengaruh Leverage, Profitabilitas dan Good Corporate Governance Terhadap Tax Avoidance: Studi Empiris pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia - Fadhilah Nurul Hanifah,; Maya Aresteria, (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The Indonesian government requires large revenues to finance development, with taxes as the main source. Although tax revenues are increasing, there are still challenges in maximizing revenues from the mining sector. Factors such as leverage, profitability, and corporate governance can affect tax avoidance practices. This study aims to examine whether leverage, profitability and good corporate governance affect tax avoidance in these companies. The population used in this study were mining companies in the energy sector listed on the Indonesia Stock Exchange (IDX). The sample was selected through purposive sampling technique, namely selective sampling based on certain objectives or characteristics of the population with a consideration. The data used in this study were obtained through the documentation method. This research is a type of descriptive quantitative research. Data analysis is in the form of multiple linear regression. In this study, variable processing was carried out using the Statistical Product and Service Solution (SPSS) software program. The results of the study indicate that leverage has a significant effect on tax avoidance. Profitability has no significant effect on tax avoidance. The independent board of commissioners has no effect on tax avoidance. Institutional ownership has no effect on tax avoidance. The audit committee has a significant effect on tax avoidance.